Las comunidades del intermareal rocoso antes y después de la eliminación de un disturbio antropogénico: un caso de estudio en las costas de Puerto Madryn (Patagonia, Argentina) - Torres, Américo Iadran (2009)
In spite of the marked growth of the coastal cities in Patagonia, studies on the effects of the urban development upon marine intertidal communities are scarce. We evaluated the rocky-shore intertidal community composition during (June 1998) and after (June 2005) exposure to a sewage discharge which was eliminated in 2001. A perturbed environment and a control site were analyzed. No significant differences were detected in species richness between sites and years. However, the species composition was different between sites in 1998 and similar in 2005. These results suggest the use of combined indicators in diagnostic studies on stressed environments.